A population-based and longitudinal study of sexual behavior and multidrug-resistant HIV among patients in clinical care. - Kozal, Michael J; Amico, K Rivet; Chiarella, Jennifer; Cornman, Deborah; Fisher, William; Fisher, Jeffrey; Friedland, Gerald (MedGenMed : Medscape general medicine, 2006)
Population-based and longitudinal information regarding sexual risk behavior among patients with multidrug resistant (MDR) HIV and their sexual partners is of great public health and clinical importance.
Keywords: Adult; Cross-Sectional Studies; Drug Resistance, Multiple, Viral; Female; HIV Infections; Humans; Longitudinal Studies; Male; Risk-Taking; Sexual Behavior